Synergistic Interaction of Ethyl Acetate Fraction of Melastoma malabathricum L. Leaves Combined with Ciprofloxacin and Gentamicin Against Eschericia coli Isolate for Diabetic Foot Ulcer Patients - Liza Pratiwi; Rafika Sari; Pratiwi Apridamayanti (Majalah Obat Tradisional, 2021)
Melastoma malabathricum leaves have active compounds that are thought to have the potential as antibacterial namely flavonoids, phenols and terpenoids. The objective of this study was to find effective drugs formulated from Melastoma malabathricum leaves combined with antibiotics as diabetic foot ulcer therapy to prevent further complications and risk of disability in diabetes mellitus patients. Ciprofloxacin and gentamicin were proven to be resistant antibiotics. In this study, the fraction of Melastoma malabathricum leaves was combined with both types of antibiotics namely ciprofloxacin and gentamicin. The minimum inhibitory concentration (MIC) has been determined against bacterial strains. The determination of MIC (Minimum Inhibitory Concentration) value was done using the Kirby-Bauer disk diffusion method. The interaction of antibiotics with gentamicin and ciprofloxacin was studied in vitro by calculating fractional inhibitory concentration index (FICI). The synergistic effects of the combination Melastoma malabathricum fraction and antibiotics were observed. The results showed that the combination of Melastoma malabathricum fraction with ciprofloxacin and the combination of Melastoma malabathricum fraction with gentamicin against Escherichia coli had a synergistic effect with FICI value of 0,5. The combination of Melastoma malabathricum fraction with ciprofloxacin and the combination of Melastoma malabathricum fraction with gentamicin have the synergistic effect inhibiting the Escherichia coli.